1997
DOI: 10.1177/0022427897034003004
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Community Policing in Nonurban America

Abstract: To date, most community policing research has taken place in large urban areas. Only a handful of studies, most using case study or small-N cross-sectional methodologies, have explored patterns of community policing in the small police agencies and nonurban areas that exist throughout much of the United States. Using data from the Justice Department's Office of Community Oriented Policing Services, this study examines levels and patterns of community policing implementation in a sample of nearly 6,000 American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 13 publications
2
60
1
Order By: Relevance
“…Agencies in the Western region have been shown to be more progressive in the adoption of community policing Maguire et al, 1997) while Zhao (1996) concluded that agencies in the Northeast region were less likely to implement. The potential influence of region on ILP is unknown as it has yet to be explored and may be sensitive to the events of September 11, 2001.…”
Section: Independent Measuresmentioning
confidence: 99%
“…Agencies in the Western region have been shown to be more progressive in the adoption of community policing Maguire et al, 1997) while Zhao (1996) concluded that agencies in the Northeast region were less likely to implement. The potential influence of region on ILP is unknown as it has yet to be explored and may be sensitive to the events of September 11, 2001.…”
Section: Independent Measuresmentioning
confidence: 99%
“…As stated by Adams et al (2005), more often than not, these smaller departments that lack empirical evaluations are those that comprise the majority of publicly funded law enforcement agencies. Moreover, since community-oriented policing is based on the idea of strengthening the social organization of communities, it is surprising that an underwhelming amount of research has been directed towards examining the relationship between the two, especially as various community characteristics might also influence styles of policing (Maguire et al 1997). The purpose of this present study is not only to determine COP's effect on violent and property crime, it is also to examine whether COP implementation can predict crime rates when controlling for social disorganization.…”
Section: Community-oriented Policing and Nonmetropolitan Communitiesmentioning
confidence: 99%
“…For example, although police in smaller agencies are reported to maintain closer ties to citizens, as well as to be better acquainted with local citizens (Liederbach and Frank, 2003), police in larger agencies engage in a wider variety of community policing activities (Maguire et al, 1997). Other studies have found that per capita expenditures (per officer and resident) are lower and clearance rates are higher in small agencies, implying greater effectiveness and efficiency than in urban jurisdictions (Falcone, Wells, and Weisheit, 2002).…”
Section: Small and Rural Agencies Law Enforcementmentioning
confidence: 99%